2022
DOI: 10.1590/1980-220x-reeusp-2022-0135en
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of systemic acupuncture in the control of urinary incontinence following radical prostatectomy: a randomized clinical trial

Abstract: Objective: To evaluate the effectiveness of acupuncture associated with pelvic floor muscle training for the control of urinary incontinence following radical prostatectomy. Method: Open-label, parallel randomized clinical trial. The intervention group (n = 33) underwent eight sessions of systemic acupuncture associated with pelvic floor muscle training and the control group (n = 31) performed only pelvic floor muscle training. The outcome variable was urinary incontinence assessed by the Pad Test and Daily P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Based on the crucial principle of 'dialectical therapy' in TCM, the depth of inserting needles was affected by the muscle thickness of the acupoints and the patient's tolerance. The retention time of needle suggested to last 20 min for all studies (Bernardes et al, 2022;Ricci et al, 2004;Yang et al, 2020;Zhang et al, 2022) reported the same.…”
Section: Discussionmentioning
confidence: 64%
“…Based on the crucial principle of 'dialectical therapy' in TCM, the depth of inserting needles was affected by the muscle thickness of the acupoints and the patient's tolerance. The retention time of needle suggested to last 20 min for all studies (Bernardes et al, 2022;Ricci et al, 2004;Yang et al, 2020;Zhang et al, 2022) reported the same.…”
Section: Discussionmentioning
confidence: 64%
“…Most authors recommended that supervised training should be performed independently at home daily [ 19 , 20 , 21 , 23 , 26 , 29 , 32 , 37 , 42 , 46 ] and that supervised training is much more effective and long-lasting than unsupervised PFMT. In most studies, home PFMT consisted of three sets of 10 [ 37 ], 15 [ 43 ], or 20 PFM contractions in a single session [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Combining deep abdominal muscle and PFM activation increased the effectiveness of PFMT and reduced UI symptoms [ 28 ]. PFMT could be combined also with acupuncture [ 20 ]. A detailed description of the analyzed studies is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations